To rewrite \((2x + 9)(x - 3)\) using the distributive property, we need to distribute each term in the first parenthesis with each term in the second parenthesis.
-
Distribute \(2x\) to both terms in \((x - 3)\): \[ 2x \cdot x = 2x^2 \] \[ 2x \cdot (-3) = -6x \]
-
Distribute \(9\) to both terms in \((x - 3)\): \[ 9 \cdot x = 9x \] \[ 9 \cdot (-3) = -27 \]
Now combine all the results: \[ 2x^2 - 6x + 9x - 27 \]
Now, combine like terms: \[ 2x^2 + ( -6x + 9x ) - 27 = 2x^2 + 3x - 27 \]
Therefore, the expression rewritten using the distributive property is: \[ 2x^2 + 3x - 27 \]